Gerakan KASBI dalam Menuntut Kenaikan UMP di Jakarta Tahun 2022 - Iqbal, Yaser; Ramadhan, Muhammad Syahrul; Saputra, Reifazmy Haidar (Journal of Politics and Democracy, 2023)
This journal reviews the Movement of the Congressional Alliance of Indonesian Trade Unions (KASBI) in demanding an increase in the DKI Jakarta UMP in 2022. The Government together with the House of Representatives are authorized to increase subsidized fuel prices, this of course invites a lot of criticism and resistance from the community, especially labor groups . For this reason, a labor movement (KASBI) was born which was held accountable for their dissatisfaction with the wages they received and policies that continued to harm their lives. According to KASBI, an increase in fuel prices will have a domino effect on all basic needs and economic growth. So that KASBI demanded an increase in UMP in response to the increase in fuel prices. Apart from that, KASBI also demanded that BBM be canceled, prices of basic commodities reduced, and the Omnibus Law repealed. However, the demands made by KASBI are certainly contrary to the interests of the entrepreneurs. The research method used in this journal is descriptive qualitative, because data collection is done by interviewing and using references to previous reading sources. The aim of the study was to find out about KASBI's movement in demanding an increase in the DKI Jakarta UMP in 2022. The results of this study indicate that the efforts and strategies undertaken by KASBI in demanding an increase in the UMP to be followed up, have not been fully realized. The government together with the House of Representatives are only of the opinion that there will be no further action regarding the demands in the mass action by KASBI.